Pillar capital of the octagonal shaft pillars of the Mukhamandapa - Temples of India Project Team (Jio Institute, 2024)
This is the pillar capital of the octagonal shaft pillars of the mukhamandapa (front porch) of the Neelkanth Mahadev Temple. The circular shaft ends in a four-sided bracket with bharavahaka (load bearer) sculptures. Just below the capital are broken elephant heads that must have supported a torana (arched gateway).